صورة الأنا والآخر في قصائد مختارة من ديوان (أَخاديدُ عُمْر) لفوزية شنة دراسة فنية - خولة بلابل; عائشة سايح; فاطمة الزهراء برقوق (University of El-oued, 2025)
تعتبر ثنائية الأنا والآخر من المفاهيم المركزية في الأدب، حيث تعكس العلاقة بين الذات والغير، وتظهر التفاعل بين الفرد ومحيطه الثقافي والاجتماعي، أما في الشعر، تجسد هذه الثنائية من خلال الصور الفنية والتعبيرات الرمزية التي تعكس الصّراع والتكامل بين الذات والآخر. -فالشاعرة فوزية شنة تظهر في قصائدها صورة الذات ككائن حساس ومؤمن بقيم الحب والجمال.تُعبّر عن مشاعرها الداخلية وتفاعلاتها مع العالم من حولها، مما يظهر عمق تجربتها الذاتية وتفردها. -أما الآخر يُصوّر في قصائدها ككائن متنوع، يتراوح بين الحبيب والمجتمع والطبيعة، تظهر الشاعرة تفاعلها مع هذا الآخر من خلال مشاعر الحب، الفقد، والتأمّل، مما يعكس تأثيره العميق على تجربتها الشعرية. -ومن خلال اطّلاعنا على قصائد الشاعرة لمسنا استخدامها تقنيات شعرية مثل: الاستعارة، التكرار والتوازن الموسيقي، لخلق صور فنية تعبر عن العلاقة بين الأنا والآخر، تظهر هذه التقنيات قدرتها على تحويل التجربة الذاتية إلى تجربة جمالية تلامسي وجدان القارئ The duality of self and other is a central concept in literature, reflecting the relationship between the self and the other and demonstrating the interaction between the individual and their cultural and social environment. In poetry, this duality is embodied through artistic images and symbolic expressions that reflect the conflict and integration between the self and the other. In her poems, the poet Fawzia Shannah depicts the self as a sensitive being who believes in the values of love and beauty. She expresses her inner feelings and interactions with the world around her, revealing the depth and uniqueness of her personal experience. The other is depicted in her poems as a diverse being, ranging from the beloved, society, and nature. The poet demonstrates her interaction with this other through feelings of love, loss, and contemplation, reflecting its profound impact on her poetic experience. Through our examination of the poet's poems, we noticed her use of poetic techniques such as metaphor, repetition, and musical balance to create artistic images that express the relationship between the self and the other. These techniques demonstrate her ability to transform the personal experience into an aesthetic one that touches the reader's conscience.
مذكرة .ماستر . أدب حديث ومعاصر. 2025
Keywords: الأنا، الآخر، الصمود، المحبة، المتيم، العشق، الأمل، الحياة، الفراق; Self; other; resilience; love; infatuated; passion; hope; life; separation.